Impact of number of functional teeth on independence of Japanese older adults. Issue 12 (21st November 2022) - Maekawa, Kenji; Ikeuchi, Tomoko; Shinkai, Shoji; Hirano, Hirohiko; Ryu, Masahiro; Tamaki, Katsushi; Yatani, Hirofumi; Kuboki, Takuo; ,; Kimura‐Ono, Aya; Kikutani, Takeshi; Suganuma, Takashi; et al.
Abstract : Aim: To examine the relationship between the number of present and functional teeth at baseline and future incidence of loss of independence. Methods: Participants were community‐dwelling older individuals who participated in a comprehensive geriatric health examination conducted in Kusatsu town, Japan, between 2009 and 2015. The primary endpoint was the incidence of loss of independence among participants, defined as the first certification of long‐term care insurance in Japan. The numbers of present and functional teeth at baseline were determined via an oral examination. Demographics, clinical variables (e.g., history of chronic diseases and psychosocial factors), blood nutritional markers, physical functions, and perceived masticatory function were assessed. Results: This study included 1121 individuals, and 205 individuals suffered from loss of independence during the follow‐up period. Kaplan–Meier estimates of loss of independence for participants with smaller numbers of present and functional teeth were significantly greater than for those with larger numbers of teeth. Cox proportional hazard analyses indicated that a smaller number of present teeth was not a significant risk factor after adjusting for demographic characteristics. However, the number of functional teeth was a significant risk factor after the adjustment (hazard ratio: 1.975 [1.168–3.340]). Additionally, higher hazard ratios were observed in other adjusted models, but they were not statistically significant. Conclusions: The number of functional teeth may be more closely related to the future incidence of loss of independence than the number of present teeth. This novel finding suggests that prosthodontic rehabilitation for tooth loss possibly prevents the future incidence of this life‐event. Geriatr Gerontol Int 2022; 22: 1032–1039 .